Subject Review: Pharmacology and Therapeutics of Anti-sense Oligodeoxynucleotides (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The purpose of this review is to provide pharmacists and pharmacologists with a background information about current therapeutic potentials and clinical trials on the anti-sense oligonucleotides (AS oligos). Anti-sense oligonucleotides are short, modified single stranded DNA or RNA that hybridize with target mRNA and inhibit synthesis of encoded peptide. This inhibition is achieved by either degradation of target mRNA by RNase enzyme or by blocking translation. The specificity of hybridization makes anti-sense treatment an attractive strategy to selectively modulate the expression of genes involved in the pathogenesis of diseases. Anti-sense oligos have now reached phase I and II in clinical trials for the treatment of cancer and viral infections. One anti-sense drug has been approved for local treatment of retinitis induced by cytomegalovirus. A number of important challenges for the development of anti-sense oligonucleotides in the clinical use have been identified, including stability, cellular uptake, target sequence selection, oligonucleotide: protein interactions, and cost of manufacture.